Age-Related Increase of Collagen/Fibrin Deposition and High PAI-1 Production in Human Nasal Polyps - Jo, Ara; Choi, Tae Gyu; Han, Jung Yeon; Tabor, Mark H.; Kolliputi, Narasaiah; Lockey, Richard F.; Cho, Seong H. (Frontiers in Pharmacology, 2022)
Objective: Our previous studies showed an age-related increased prevalence of nasal polyps (NP) and reduced production of S100A8/9 in elderly patients with chronic rhinosinusitis with NP (CRSwNP). In this study, we investigated an unbiased age-related gene expression profile in CRSwNP subjects and healthy controls, and further identified the differences in their tissue remodeling. Methods: Microarrays using NP and uncinate tissues from health controls (elderly, age ≥65 vs. non-elderly, age 18-49) were performed, and differentially regulated genes were analyzed. Quantitative real-time PCR (qPCR), Immunostaining, Periodic acid-Schiff (PAS), trichrome staining, Western blot, and ELISA were performed for further investigation. Results: Microarrays identified differentially expressed genes according to disease and age; 278 in NP vs. controls, 75 in non-elderly NP vs. non-elderly controls, and 32 in elderly NP vs. elderly controls. qPCR confirmed that the PLAT gene was downregulated and the SERPINB2 gene upregulated in NP vs. controls. The serous glandular cell-derived antimicrobial protein/peptide-related genes such as BPIFB3, BPIFB2, LPO, and MUC7 were remarkably reduced in NP, regardless of age. SERPINE1 gene (plasminogen activator inhibitor-1, PAI-1) expression was significantly increased in elderly NP versus elderly controls. IHC and western blot confirmed significantly decreased production of MUC7 and LPO in NP versus controls. There was a trend of age-related reduction of submucosal gland cells in normal controls. Trichrome and immunofluorescence staining demonstrated an age-related increase of collagen and fibrin deposition in NP, consistent with increased PAI-1 production. Conclusion: This study demonstrated age-related differential glandular remodeling patterns and fibrosis in NP and normal controls. PAI-1 expression was significantly increased in elderly NP versus elderly controls, suggesting PAI-1 as a potential treatment target in elderly NP.